Concept of «Competency» and «Competence» in the Context of the Competence-Based Approach in Education - Zaredinova, Elvira; Ziyadinova, Rimma (Pedagogical Discourse, 2013)
Analysis of the views of scientists to the definition of the term «competence» and «competency» is done in the article, various approaches to the interpretation of the concepts in the context of the competence-based approach to education are studied. Analysis of the views of scientists to identify the essence of the notion « competence « and «competency» has shown that the substance of the mentioned concepts and their diffierentiation is treated differently. The article made an attempt to analyze and summarize the diversity of approaches to the problem.